SAT0072 Functional Disability: A Parameter Fit to BE A Biomarker for Inflammatory Arthritis. (10th June 2014) - El Miedany, Y.; El Gaafary, M.; Sayed, S.; Nasr, A.; Palmer, D.
Abstract : Background: The search for markers identifying key targets for the assessment of major outcomes in Rheumatoid Arthritis (RA) has become one of the hot issues in rheumatology. Possible markers should help to identify (in early RA) the patients who are going to respond quickly to therapy with the opportunity to tailor management to the patient status. So far this target has not been achieved. Objectives: To assess whether Functional Disability can be used as a valid biomarker enabling the physicians to optimally match patient with disease progression and response to treatment. Methods: Retrospective study which included 481 subjects suffering from early inflammatory arthritis (Disease duration <6-months) diagnosed according to the ACR/EULAR criteria 2010. Changes from baseline to week 76 in clinical variables, patient reported outcome measures [1], including functional disability, and measures of radiographic progression were assessed in early RA patients diagnosed according to the 2010 EULAR/ACR criteria for RA and treated to Target. Radiographic progression was scored at baseline and at 76-weeks using modified Sharp score as well as US scores for number of erosions, synovial hypertrophy and vascularity (using Power Doppler). Biochemical laboratory measures included ESR, CRP and rheumatoid factor. Correlation of functional disability score to response to therapy at 3, 6 and 12 months of management as well as to work ability, development of erosions and joint affection were studied. The sensitivity and specificity of Functional disability as an indicator of prognosis was also assessed using ROC curve analysis. Results: The crude functional disability score as well as the percentage changes at 3 and 6 months showed a statistically significant increase in the group with persistent inflammatory synovitis compared to the self-limiting arthritis group. Using binary logistic regression analyses to assess the association between functional disability and disease activity flare up revealed that a flare was associated with poor baseline function and quality of life measures: Functional disability [OR per 0.1 unit=1.8 (1.06–1.54), p=0.004] and Quality of Life [OR=1.12 (1.01–1.23), p=0.024]. Changes in functional disability scores were not significantly correlated to changes in inflammatory biochemical markers (ESR and CRP) levels. However, changes in the functional disability scores correlated significantly to changes in PD scores (p<0.01). In multiple conditional logistic regression analysis, factors associated with the development of joint space narrowing were worsening of functional disability score by >0.5/3, synovial thickening and synovial PD score ≥2 at both baseline and 6-months of treatment. The discriminative power had an AUC of 0.864 (95% CI 0.765 - 0.937), with Sensitivity 84%, Specificity 92% and LR + 5.6. Conclusions: Functional disability met the criteria of a valid marker for rheumatoid arthritis, being objectively measured, indicator of normal and pathologic joint affection, as well as a sensitive and specific marker for response to therapy and poor prognosis. References: Incorporating patient reported outcome measures in clinical practice: development and validation of a questionnaire for inflammatory arthritis. Clin Exp Rheumatol. 2010; 28(5):734. Acknowledgements: To Omar El Miedany for help in data recording and admin support. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.1470